Research-Relevant Clinical Pathology Resources: Emphasis on Mice, Rats, Rabbits, Dogs, Minipigs, and Non-Human Primates. (6th December 2021) - Bau-Gaudreault, Liza; Arndt, Tara; Provencher, Anne; Brayton, Cory F
Abstract: Clinical pathology testing for investigative or biomedical research and for preclinical toxicity and safety assessment in laboratory animals is a distinct specialty requiring an understanding of species specific and other influential variables on results and interpretation. This review of clinical pathology principles and testing recommendations in laboratory animal species aims to provide a useful resource for researchers, veterinary specialists, toxicologists, and clinical or anatomic pathologists.